Зрівняння розробки для iOS та Android в контексті сучасних мобільних технологій - Бєгунова, В. Д. (ХНУРЕ, 2025)
The work compares the main differences between developing mobile appli-cations for iOS and Android platforms. It analyzes the features of each platform’s ecosystem, including the choice of programming languages, development envi-ronments, and user interface design requirements. It discusses the benefits and challenges that developers face, including issues of performance, stability, testing, and adaptation of applications to different devices. It also focuses on the features of publishing applications on the App Store and Google Play. The study allows us to better understand what factors influence the choice of approach to developing mobile applications depending on business needs and user expectations.
Keywords: мобільна технологія; iOS platform; Android platform